Hizbiyyah and Hizbut Tahrir Indonesia's New Member Recruitment Strategy After Disbandment - Rahman, Mohammad Taufiq; Bukhori, Bukhori; Setia, Paelani (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2023)
This article discusses Hizbut Tahrir Indonesia's new member recruitment strategy after the government disbanded them through Perppu on Community Organization Number 2 of 2017. The research method used is qualitative through data collection, observation, interview, and document review. This research found that Hizbut Tahrir Indonesia changed its strategy from open recruitment to using strategies through informal groups and individuals in recruiting members behind closed doors, especially after they were banned by the government in 2017, namely through the student movement, through the activities of figures in mosques, and women. According to HTI, these three strategies have a safe tendency because they can be done secretly and escape the control of the government and mass organizations that oppose them. According to HTI, the student movement is considered necessary because they are educated citizens who have the potential to become agents of change in society. Meanwhile, the mosque is the center of Muslim activity, where the recruitment of DKM administrators, preachers, and congregants can accelerate the preaching of the Khilafah. Meanwhile, the use of women as another HTI recruitment agent is done because the HTI doctrine believes in the importance of women as pillars of civilization. This article argues that although the government has banned HTI, they are still fighting back, mainly through invisible and covert means.